2014
DOI: 10.1155/2014/215471
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Regulatory B Cells in Cancer

Abstract: Regulatory B cells (Bregs), a newly described subset of B cells, have been proved to play a suppressive role in immune system. Bregs can inhibit other immune cells through cytokines secretion and antigen presentation, which give them the role in the pathogenesis of autoimmune diseases and cancers. There are no clear criteria to identify Bregs; different markers were used in the different experimental conditions. Massive researches had described the functions of immune cells such as regulatory T cells (Tregs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 62 publications
1
56
0
Order By: Relevance
“…13 Since these seminal observations, a considerable body of evidence has conclusively demonstrated the significance of IL-10-producing Bregs in diverse murine models and human studies of autoimmunity, infection, and cancer. [14][15][16][17][18][19][20] More recently, there have also been reports of the role of Bregs in human cGVHD. 18,19 To date, the limited number of cell surface antigens studied and the lack of consensual definitions of the Breg subset phenotype have impeded direct comparison of human B-cell subsets with regulatory function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Since these seminal observations, a considerable body of evidence has conclusively demonstrated the significance of IL-10-producing Bregs in diverse murine models and human studies of autoimmunity, infection, and cancer. [14][15][16][17][18][19][20] More recently, there have also been reports of the role of Bregs in human cGVHD. 18,19 To date, the limited number of cell surface antigens studied and the lack of consensual definitions of the Breg subset phenotype have impeded direct comparison of human B-cell subsets with regulatory function.…”
Section: Introductionmentioning
confidence: 99%
“…In murine models, B cells with regulatory function were found within CD1d hi CD5 1 (B10) cells, mesenteric lymph node B cells, marginal zone B cells, T2 2 marginal zone precursor cells, and Tim-1 1 Bregs. 17,21,22 In humans, Blair and coworkers have described Bregs as CD19 1 CD24 hi CD38 hi , a phenotype that normally defines human transitional B cells, 21,22 whereas other lines of evidence indicate that human Bregs, identified through IL-10 intracellular staining, are contained within the CD24 hi CD27 1 B-cell subset 19,23 or within both the memory (CD27 1 ) and transitional (CD38 hi ) B-cell compartments. 24 We recently reported that Bregs are enriched within both the transitional and immunoglobulin M (IgM) memory B-cell subsets in human peripheral blood (PB), and mediate suppression of T-cell proliferation and effector cytokine production through both IL-10-dependent and cell-cell contact-dependent mechanisms (mainly involving CD80/CD86).…”
Section: Introductionmentioning
confidence: 99%
“…IL-10, a major factor of human B cell activation, proliferation, and differentiation (8), is also a key immunosuppressive cytokine of regulatory B cells (Bregs), a B cell subset that supports immunological tolerance (9,10). Bregs contribute to immune suppression during various infectious diseases or in pathogenesis of autoimmune and neoplastic disorders (11)(12)(13). Breg properties are related to a variety of mechanisms, including secretion of antiinflammatory and immunosuppressive molecules such as IL-10, IL-35, and TGF-b1, or expression of the immunosuppressive molecule PD-L1.…”
mentioning
confidence: 99%
“…2, 3 At present, the role of Bregs in cancers, including MM, has not been fully studied. 4 Here we phenotypically define Bregs in MM and examine their role in mediating immunosuppression, which is a hallmark of this disease. The detailed methods are described in the Supplementary Material.…”
mentioning
confidence: 99%